Awareness of building occupant on emergency response plan in office building / Aliff Khusairy Mohd Amin - Mohd Amin, Aliff Khusairy (2009)
Emergency response plan is not a new system in Malaysia. This plan is important in a building especially in office building, because fire is something that unpredictable that can happen anytime.